Coffee and caffeine consumption and risk of renal cell carcinoma: A Mendelian randomization study - Li, Bing-Hui; Yan, Si-Yu; Li, Xu-Hui; Huang, Qiao; Luo, Li-Sha; Wang, Yun-Yun; Huang, Jiao; Jin, Ying-Hui; Wang, Yong-Bo (Frontiers in Nutrition, 2022)
Background: The association between coffee and caffeine consumption and risk of renal cell carcinoma was inconsistent among observational studies, and whether these observed associations were causal remained unclear. Therefore, we performed a two-sample Mendelian randomization (MR) study to assess the causal nature of the association. Methods: Twelve and two independent single nucleotide polymorphisms (SNPs) related with coffee and caffeine consumption at genome-wide significance level of P < 5×10-8 were used as instrumental variables (IVs), respectively. Summary-level data for renal cell carcinoma were taken from the FinnGen consortium with up to 174,977 individuals and the International Agency for Research on Cancer (IARC) with 13,230 individuals. We used inverse-variance weighted (IVW) as main method, followed by weighted median method, MR-Egger regression method, and MR robust adjusted profile score method. Outlier and pleiotropic variants were assessed by MR Pleiotropy RESidual Sum and Outlier test and MR-Egger regression. We used meta-analysis methods in fixed-effects to combine the estimates from the two sources. Results: The genetically predicted coffee consumption was not associated with the risk of renal cell carcinoma in the FinnGen consortium, and the relationship was consistent in the IARC consortium. The pooled odds ratio (OR) of per 50% increase of coffee consumption was 0.752 (95% confidence interval (CI), 0.512-1.105; P=0.147). In addition, complementary analyses that separated the coffee-related SNPs according to their relationship with blood levels of caffeine metabolites (higher, lower, or unrelated) found no relationship with renal cell carcinoma. The remaining four SNPs as IVs for coffee consumption by excluded eight SNPs due to potential risk factors at genome-wide significance (P<5×10−8) showed consistent results. Moreover, per a genetically predicted 80-mg increase in caffeine consumption was not associated with the risk of renal cell carcinoma (pooled OR = 0.872, 95% CI: 0.676-1.125, P=0.292). Conclusions: Our MR study provided no convincing evidence for a causal effect between coffee and caffeine consumption and risk of renal cell carcinoma. The associations for renal cell carcinoma need to be verified in well-powered studies.